Gender differences in the kinematics and ball velocity of overarm throwing in elite team handball players - van den Tillaar, R.; Cabri, J. M. H. (Journal of Sports Sciences, 2012)
The aim of this study was to investigate the throwing velocity and kinematics of overarm throwing in team handball of elite female and male handball players. Kinematics and ball velocity of a 7 metre-throw in eleven elite male (age 23.6 ± 5.2 yr, body mass 87.0 ± 6.8 kg, height 1.85 ± 0.05 m) and eleven elite female (age 20.3 ± 1.8 yr, body mass 69.9 ± 5.5 kg, height 1.75 ± 0.05 m) team handball players were recorded. The analysis consisted of maximal joint angles, angles at ball release, maximal angular velocities of the joint movements, and maximal linear velocities of the distal endpoints of segments and their timing during the throw. The ball release velocity of the male handball players was significantly higher than the females (21.1 vs. 19.2 m · s-1; p < 0.05). No major differences in kinematics were found, except for the maximal endpoint velocities of the hand and wrist segment, indicating that male and female handball players throw with the same technique. It was concluded that differences in throwing velocity in elite male and female handball players are generally not the result of changes in kinematics in the joint movements.